2018
DOI: 10.1097/wco.0000000000000527
|View full text |Cite
|
Sign up to set email alerts
|

PET and ictal SPECT can be helpful for localizing epileptic foci

Abstract: Purpose of reviewFunctional neuroimaging with PET and SPECT is a commonly used tool in presurgical evaluation. The following article reviews the literature of PET and SPECT in presurgical assessment of epilepsies published in the last year.Recent findingsFDG-PET adds concomitant information in temporal and extratemporal lobe epilepsy in adults and children. The pattern of hypometabolism in FDG-PET is a good additional predictor or seizure outcome in TLE with mesial temporal sclerosis or negative MRI. There is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
54
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 60 publications
1
54
0
1
Order By: Relevance
“…Therefore, it is used as a complementary rather than alternative technique to SISCOM. [28][29][30][31] In our study, SISCOM could localize the PEZ in 27.8% of the patients with noninformative MRI. In the study by Perissinotti et al, SISCOM was able to localize the PEZ in 57.6% of the patients with noninformative MRI.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Therefore, it is used as a complementary rather than alternative technique to SISCOM. [28][29][30][31] In our study, SISCOM could localize the PEZ in 27.8% of the patients with noninformative MRI. In the study by Perissinotti et al, SISCOM was able to localize the PEZ in 57.6% of the patients with noninformative MRI.…”
Section: Discussionmentioning
confidence: 64%
“…It should be stressed that FDG‐PET does not visualize the seizure onset zone, but the functional deficit zone. Therefore, it is used as a complementary rather than alternative technique to SISCOM …”
Section: Discussionmentioning
confidence: 99%
“…In our case, prominent hyperperfusion in the right cortex was shown on the brain perfusion SPECT, which was done on the day of the seizure ( Figure 1 ). Hyperperfusion in the seizure focus on brain perfusion SPECT on the ictal timing is a well-known feature [ 11 ]. In our case, hyperperfused lesions on brain SPECT were strongly correlated with the lesions shown by MRI changes – T2 hyperintensity with mild diffusion restriction ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that rapid spread of epileptic activities could result in widespread hypometabolism, sometimes remote to the EZ. Diffuse regions of hyperperfusion might reflect the epileptic network which includes the epileptic focus as well as the propagation pathways away from the onset, further complicating the task of localization ( 25 ). Although MEG has theoretical advantages including high spatial and temporal resolution in identifying epileptic activities from deep structures compared to scalp EEG ( 26 ), its localization seemed to be limited for CC as shown in our study, perhaps due to the CC producing radially oriented sources difficult to be detected by MEG source localization.…”
Section: Discussionmentioning
confidence: 99%